Empowering Garut's Entrepreneurs: A Community Engagement Initiative through the WiraHebat Digital Marketing Training - Asep Koswara (Community Development and Empowerment, 2025)
This study reports on a community service activity aimed at enhancing the digital capability of MSME actors in Garut, Indonesia, conducted on November 19, 2025, as part of the WiraHebat Goes to Village program. Addressing the local digital gap, the intervention utilized a practitioner-led training titled, "Digital Marketing for UMKM & Entrepreneurs: Mindset, Strategi, dan Aksi". The methodology employed presentation, Q&A, and brainstorming, with evaluation based on qualitative feedback. Results confirmed a successful paradigm shift in the entrepreneurial mindset and high conceptual comprehension of the Hybrid Strategy and 4P diagnostic tool. Participants showed keen interest in local channels like website, social media, eCommerce, marketplace and Google My Business (GMB). The activity successfully initiated Digital Empowerment, validating the approach of strengthening strategic thinking (Mindset and Strategy). However, a significant technical execution gap (Action Gap) was identified due to the one-day format. The conclusion recommends mandatory, phased technical mentoring following the training to ensure the conceptual gains translate into measurable economic performance and sustainable business growth for the WiraHebat partners.